\(\Rightarrow\)2x-1 \(\in\)Ư(11)={-1;-11;1;11}
Ta có bảng giá trị
2x-1 | -1 | -11 | 1 | 11 |
2x | 0 | -10 | 2 | 12 |
x | 0 | -5 | 1 | 6 |
Vậy x={0;-5;1;6}
Ta có: 11 chia hết cho ( 2x - 1 )
Suy ra: 2x - 1 thuộc ước của 11 = { 1; 11 }
Nêu 2x -1 = 1 suy ra 2x = 2 suy ra x = 1
Nếu 2x -1 = 11 suy ra 2x = 12 suy ra x = 6
Vậy x = 1 hoặc x =6
11 \(⋮\)2x - 1
=> 2x - 1 \(\in\)Ư ( 11 ) = { 1 ; 11 ; -1 ; -11 }
Với 2x - 1 = 1 => x = 1
Với 2x - 1 = 11 => x = 6
Với 2x - 1 = -1 => x = 0
Với 2x - 1 = -11 => x = -5
Vậy x \(\in\){ 1 ; 6 ; 0 ; -5 }
=>2x-1=11
2x=11+1
2x=12
x=12:2
x=6
vay x=6